EVALUASI SISTEM JARINGAN PIPA DISTRIBUSI AIR BERSIH DI KECAMATAN AMPEK NAGARI KABUPATEN AGAM - Zahara, Elvika; Dewi, Selpa; Hafnil, Jon (Ensiklopedia Research and Community Service Review, 2024)
Water is one of the basic needs that cannot be separated from living creatures. The location of this research is in Ampek Nagari District, Agam Regency. The aim of this research is to determine the need for clean water in the next 15 years. It needs to be analyzed by projecting the population, domestic needs, non-domestic needs, average water needs and water loss. The calculation methods used to project population numbers are arithmetic, geometric and exponential methods, while distribution network analysis uses Epanet 2.0. Based on category IV, namely small cities with household connection consumption of 130 liters/person/day, the calculation of clean water needs for PDAM Tirta Antokan for domestic needs in 2023 is 45,785 lt/sec, and in 2037 it is 46,595 lt/sec, non-negotiable needs. domestic in 2023 amounting to 6,867 lt/sec.Keywords: SR; Exponential; Geometric; Arithmetic; Epanet 2.0.